Loading Metal Nanostructures on Cotton Fabrics as Recyclable Catalysts. Issue 7 (13th December 2012) - Yang, Baocheng; Zhao, Chunmei; Xiao, Manda; Wang, Feng; Li, Chuanhao; Wang, Jianfang; Yu, Jimmy C.
<x xml:space="preserve">Abstract</x> Noble metal nanostructures of varying compositions and shapes are loaded on cotton fabrics. The fabric‐supported metal nanostructures can function as effective catalysts for different liquid‐phase catalytic reactions. They exhibit superior recyclability, with the catalytic activities remaining nearly unchanged even after ten cycles of catalytic reactions for all of the three tested reactions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>